Whitney’s jets for Sobolev functions - Bojarski, B. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We present two fundamental facts of the jet theory for Sobolev spaces W^m, p. One of them is that the formal differentiation of k-jets theory is compatible with the pointwise definition of Sobolev (m - 1)-jet spaces on regular subsets of Euclidean spaces R^n. The second result describes the Sobolev embedding operator of Sobolev jet spaces increasing the order of integrability of Sobolev functions up to the critical Sobolev exponent.